Aspectos metabólicos, fisiológicos e taxonômicos de actinomiceto produtor de exopolissacarídeos, proveniente de águas subterrâneas contaminadas (São Carlos, SP) - Fusconi, Roberta (2005)
Strains Lc (CCT 7277) and Lg (CCT 7137), isolated from landfill leachate-contaminated groundwater and found to produce exopolysaccharides (ESP), were characterized by polyphasic taxonomy. The growth and EPS production of Lg strain on sugarcane molasses, at concentrations between 2% and 10% and on the standard GYM medium were studied and its responses to nutrient starvation were analysed. Morphological, biochemical, chemotaxonomic and molecular tests indicated that Lc and Lg have properties typical of Gordonia polyisoprenivorans DSM 44303T. Viable cell counts revealed that GYM medium was the best for growth (µmax = 0,232 h-1). EPS production started during the exponential phase and continued during the stationary phase, in all culture media. After 24h of stationary phase, G. polyisoprenivorans CCT 7137 showed a highest total EPS production in 6% (172,86 g/l) and 10% (139,47 g/l) sugarcane molasses media, a highest EPS production for unit of cellular concentration in 10% sugarcane molasses medium (39,03 x 10- 11g/UFC) and a highest porcentage of free EPS in 2%, 6% e 10% sugarcane molasses media (88,37%, 62,4% e 64,22%, respectively). G. polyisoprenivorans CCT 7137 showed three responses to nutrient starvation: a decrease in the cell viability (13,7% and 3,25% after 7 and 56 days respectively), a reduction in cell size (from 0,55 to 0,33 µm3) and a cell shape change (from rod to coccobacillus). G. polyisoprenivorans CCT 7277 and CCT 7137 are two of six strains of G. polyisoprenivorans so far isolated and recorded in the literature, and the first strains found in a brazilian ecosystem. The data presented here suggest the potencial of G. polyisoprenivorans CCT7137 to be used as ultramicrobacteria in porous media experiments such as to aim for the study of sugarcane molasses as nutrient source for in situ EPS to biorremediate contaminated sites through the biobarrier technology.